(3LeY GdegeGJ GdeMJGL EdjgG aj Yde GdejbGJs
(3ChdgG (B:s
(3GdMeO ddg QajY GdOQLGJ hHYO , eQGOi ef gPG GdcJGH cjajI GdYed HGdCSWQdGH hSejJg LeY GdegeGJ GdeMJGL EdjgG ai Yde GdejbGJ , hjfMUQ GdebUhO efg ai ebOeJjf hCQHYI hYTQjf HGHkG s
(3BNQgG (B:s
(3aCjf COQGL GdWhGdY hGdChJGO ef COQGL Gdadc GfXQ cJGH GdbOeGA hfLHGA GdMceGA dJbjS Ydjg hPdc Cf eDdag EROGO YfOfG HWGdY GdLhRGA Mjf JCdja gPg GdQSGdI , aGageg hbS Ydjg JQTjO acGf GdJYOjd gcPG hbS Ydjg , hHGddg GdJhajb s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs